2007
DOI: 10.1002/ar.20615
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Neurochemistry of Descending and Ascending Myenteric Plexus Neurons of Sheep Ileum

Abstract: The specific patterns of gastrointestinal motility in large herbivores may relate to differences in the organization of enteric nerve circuits, compared with other mammals. To investigate this possibility, we characterized the morphologies, chemical phenotypes, and projections of myenteric plexus (MP) neurons of the sheep ileum. Morphologies and projections were investigated after application of the carbocyanine dye (1,1 0 , di-octadecyl-3,3,3 0 ,3 0 ,-tetramethylindo-carbocyanine perchlorate, DiI) to fixed ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
7
17
2
Order By: Relevance
“…This last population could represent a subpopulation of interneurons, expressing both phenotypes, similar to those neurons which we recently observed in the sheep ileum (Mazzuoli et al, 2007). The large percentage of nitrergic neurons innervating the sheep PS reinforces the hypothesis that NOS-IR FB-labelled neurons are responsible for inhibition of the PS musculature.…”
Section: Abomasal Innervation Of the Pssupporting
confidence: 55%
See 1 more Smart Citation
“…This last population could represent a subpopulation of interneurons, expressing both phenotypes, similar to those neurons which we recently observed in the sheep ileum (Mazzuoli et al, 2007). The large percentage of nitrergic neurons innervating the sheep PS reinforces the hypothesis that NOS-IR FB-labelled neurons are responsible for inhibition of the PS musculature.…”
Section: Abomasal Innervation Of the Pssupporting
confidence: 55%
“…Almost all nitrergic neurons were also SP-IR (98%); among these cells, about 64% innervated the PS; these could be descending inhibitory motoneurons or interneurons because we have recently observed large subpopulations of neurons expressing both NOSand SP-IR in the sheep ileum (Mazzuoli et al, 2007). Of the neurons innervating the PS, it is possible to identify at least three distinct categories of neurons: NOS/SP-IR (64%), NOS/ChAT-IR (21%), and ChAT/SP-IR (2%); we should also consider dopaminergic neurons which probably expressed only TH-IR.…”
Section: Immunohistochemical Classes and Ps Abomasal Innervationmentioning
confidence: 98%
“…The present observations show that NF immunoreactivity occurs in type II neurons in the guinea-pig, as it does in the small intestine of other species, including human (Ganns et al 2006;Brehmer 2007), pig (Barbiers et al 1995;Brehmer et al 2002), cattle (Balemba et al 1999), sheep (Mazzuoli et al 2007) and mouse (Qu et al 2008). Indeed, in each of these species, anti-NF antibodies are useful for identifying type II neurons.…”
Section: Type II Neuronsmentioning
confidence: 58%
“…Type II neurons, which are readily distinguished by their large round or oval cell bodies and multiple axons (Brehmer et al 1999;Furness 2006) are characteristically revealed by anti-NF-H antibodies in the human and pig small intestine, where this is one of the best ways to demonstrate type II neurons (Brehmer et al 2002;Ganns et al 2006;Brehmer 2007;Wolf et al 2007). Anti-NF antibodies are also ideal for the localisation of type II neurons in cattle (Balemba et al 1999), sheep (Mazzuoli et al 2007) and mice (Qu et al 2008). In marked contrast, two previous studies found that type II neurons in the guineapig enteric nervous system were not NF-immunoreactive (Costa et al 1996;Hu et al 2002), although other neurons with NF immunoreactivity were reported in both studies.…”
Section: Introductionmentioning
confidence: 82%
“…Specimens were embedded in OCT compound (Tissue-Tek Sakura, Torrance, Calif., USA), frozen in liquid nitrogen and cut into 12- to 14-µm-thick sections using a cryostat. Sections were then processed for double-labeling indirect immunofluorescence as described previously [39, 40]. Briefly, sections were washed in PB, incubated in 10% normal goat serum for 1 h at room temperature and then incubated overnight at 4°C with the following mixtures containing: rabbit polyclonal anti-A 1 adenosine receptor (1:100; Sigma-Aldrich Chemie, Steinheim, Germany) and either mouse monoclonal anti-HuC/D (1:200; Molecular Probes Inc., Eugene, Oreg., USA) or anti-nNOS (1:200, Santa Cruz Biotechnology, Santa Cruz, Calif., USA), a general neuronal marker and a major inhibitory neurotransmitter, respectively.…”
Section: Methodsmentioning
confidence: 99%